IMPACT OF PREVENTIVE PRACTICES ON ANAEMIA DUE TO MALARIA AMONG CHILDREN ATTENDING OUT-PATIENT CLINIC IN SPECIALIST HOSPITAL YOLA, ADAMAWA STATE, NIGERIA - Ishaku, Nassai; Kunihya, I. Z.; Seni, J. B.; Justine, L. D.; Sarki, A. (FUDMA JOURNAL OF SCIENCES, 2020)
The study focused on the impact of preventive practices on anaemia due to malaria among children. The study considered Out-Patients children who came to laboratory for malaria diagnostic test. Blood sample was examined using Giemsa stain for parasite detection and speciation. Informed consent was obtained and structured questionnaire were administered. Pack Cell Volume was used to screened for anaemia. A total of 310 children were sampled. Malaria anaemia in relation to types of net used, children that were anaemic with malaria used damage insecticide nets recorded highest and least among those using untreated insecticide net with 57.1% and 38.0% respectively (pËƒ0.05). Malaria anaemia based on insecticide application, those used cover cloth (50.0%) against mosquito vector and are anaemic with malaria recorded highest while those applied house spray (25.0%) had the least. Malaria anaemia with regard to sleeping habit of the child at night, high proportion were seen in children that were anaemic with malaria sleeping outdoor (56.5%) while those sleeping indoor (36.9%) recorded least (pËƒ0.05). Subjects that were anaemic with malaria and previously used Sulphonamides (51.4%) had highest prevalence (pËƒ0.05). Children that were anaemic with malaria and period of last treatment of four months (58.2%) recorded highest while period of last treatment of one month (24.1%) had the least (pËƒ0.05). Therefore, insecticide application using house spray, stayed indoor at night using mosquito nets had an impact on reducing the risk of anaemia due to malaria.